PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL KOOPERATIF BERBASIS KONTEKSTUAL DAERAH PESISIR PADA SISWA KELAS VII SMP NEGERI 1 KAPONTORI - Abdul Manaf (IAIN Ambon, 2016)
The present research is a developmental research aimed to produce mathematics instructional package using Coastal Area Based Cooperative Model satisfying criteria of valid, practice, and effective. The product to be made was a valid, practice, and effective instructional package. The product consists of Lesson Plan, Students’ Book, Teacher’s Book, Students’ Worksheet, and Learning Achievement Test. The process of instructional package development used model of 4-D Thiagarajan consisting of 4 steps namely define, design, develop, and disseminate. The research suggests that the instructional package is cosiderably valid, practice, and effective based on the assessment of the validator and the try-out. The validity score of instructional package was obtained from the measurement used by the validators satisfying the criteria of valid, i.e. (1) Lesson Plan with average of 3,45 (2) Students’ Book with average of 3,6 (3) Teacher’s Book with average of 3,35 (4) Studetns’ Worksheet with average of 3,55 and (5) Learning Achievement Test with average of 3,59. It shows that the instructional package satisfies valid category. The practicality of the instructional package was measured based on the implementation observation of the instructional package in classroom shown by the fulfillment of 4 indicators of effectiveness i.e. : (1) the percentage of the average of classical completeness is 85,71%, (2) the fulfillment of 8 categories of students’ activities, (3) more than 80% of students giving positive response to the learning, (4) the ability of teachers in managing the managing is in good criterion. Key Words: Development of mathematics instructional, package using coastal area, cooperative model